Disturbed Red Blood Cell Structure and Function: An Exploration of the Role of Red Blood Cells in Neurodegeneration - Bosman, Giel J. C. G. M. (Frontiers in Medicine, 2018)
The structure of red blood cells is affected by many inborn and acquired factors, but in most cases this does not seem to affect their function or survival in physiological conditions. Often, functional deficits become apparent only when they are subjected to biochemical or mechanical stress in vitro, or to pathological conditions in vivo. Our data on the misshapen red blood cells of patients with neuroacanthocytosis illustrate this general mechanism: an abnormal morphology is associated with an increase in the susceptibility of red blood cells to osmotic and mechanical stress, and alters their rheological properties. The underlying mutations may not only affect red cell function, but also render neurons in specific brain areas more susceptible to a concomitant reduction in oxygen supply. Through this mechanism, an increased susceptibility of already compromised red blood cells to physiological stress conditions may constitute an additional risk factor in vulnerable individuals. Also, susceptibility may be induced or enhanced by systemic pathological conditions such as inflammation. An exploration of the literature suggests that disturbed red blood cell function may play a role in the pathophysiology of various neurodegenerative diseases. Therefore, interventions that reduce the susceptibility of red blood cells to physiological and pathological stress may reduce the extent or progress of neurodegeneration.